2021
DOI: 10.1186/s12885-021-08903-4
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum and oral cancer: a critical review

Abstract: There is a growing level of interest in the potential role inflammation has on the initiation and progression of malignancy. Notable examples include Helicobacter pylori-mediated inflammation in gastric cancer and more recently Fusobacterium nucleatum-mediated inflammation in colorectal cancer. Fusobacterium nucleatum is a Gram-negative anaerobic bacterium that was first isolated from the oral cavity and identified as a periodontal pathogen. Biofilms on oral squamous cell carcinomas are enriched with anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 112 publications
2
40
0
Order By: Relevance
“…Other studies have reported changes in microbial oral flora in patients with oral carcinomas (Martin and van Saene, 1992;Nagy et al, 1998;Anjali et al, 2020) and during radiation treatment (Llory et al, 1972;Brown et al, 1975;Keene et al, 1981;Keene and Fleming, 1987;Epstein et al, 1991;Abu Shara et al, 1993;Leung et al, 2001;Vissink et al, 2003b;Dahlen et al, 2009;Anjali et al, 2020;Zagury-Orly et al, 2021). These changes have also included an increase in Fusobacterium and Veillonella (Nagy et al, 1998;McIlvanna et al, 2021;Minarovits et al, 2021), as was found in this study.…”
Section: Discussionsupporting
confidence: 67%
“…Other studies have reported changes in microbial oral flora in patients with oral carcinomas (Martin and van Saene, 1992;Nagy et al, 1998;Anjali et al, 2020) and during radiation treatment (Llory et al, 1972;Brown et al, 1975;Keene et al, 1981;Keene and Fleming, 1987;Epstein et al, 1991;Abu Shara et al, 1993;Leung et al, 2001;Vissink et al, 2003b;Dahlen et al, 2009;Anjali et al, 2020;Zagury-Orly et al, 2021). These changes have also included an increase in Fusobacterium and Veillonella (Nagy et al, 1998;McIlvanna et al, 2021;Minarovits et al, 2021), as was found in this study.…”
Section: Discussionsupporting
confidence: 67%
“…Because OLP is potentially cancerous, there is a risk that these bacteria may promote the conversion of OLP into OSCC, even if it is not clear whether these bacteria are the cause or result of OLP. Bacteria of Fusobacterium and Porphyromonas are mainly studied so far, both of which can promote the occurrence and development of OSCC through various mechanisms ( Li et al, 2020 ; Mcilvanna et al, 2021 ; Vyhnalova et al, 2021 ). The dominant bacteria of OSCC were different in different regions and stages ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This experimental periodontitis model was initiated by a 5-day placement of a ligature around the second maxillary molar tooth, followed by oral inoculation of Fusobacterium nucleatum to promote prolonged inflammation and dysbiosis. F. nucleatum can act as an anchoring perio-pathogen to initiate and support periodontitis biofilm formation ( Foster and Kolenbrander, 2004 ; Park et al, 2016 ; Thurnheer et al, 2019 ; Yamada et al, 2005 ; Yip et al, 2021 ) and induce chronic inflammation and immune evasion locally and systemically ( Hajishengallis and Chavakis, 2021 ; McIlvanna et al, 2021 ). Thus, by adapting the traditional ligature-induced PD model, we can examine initiating events in PD and later events because of prolonged inflammation and dysbiosis.…”
Section: Resultsmentioning
confidence: 99%